Impact of Domestic Wastewater Discharge on Organic Load and Thermotolerant Coliforms in the Ichu River, Central Highlands of Peru - Ortega-Quispe, Kevin; Enriquez-Pinedo, Lucía; Aliaga-Rojas, María; Carbajal Quispe, Nisbeth; Solis-Porras, Eybi; Ccopi-Trucios, Dennis (Peruvian Agricultural Research, 2025)
Objective: This study aimed to evaluate the impact of domestic wastewater discharge on the organic load and presence of thermotolerant coliforms in the Ichu River, located in the central highlands of Peru. Methodology: Water samples were collected at two points in the river, both upstream and downstream. The sample collection followed national protocols for water quality monitoring, and the samples were then analyzed to determine the levels of Biochemical Oxygen Demand (BOD5), Chemical Oxygen Demand (COD), thermotolerant coliforms, and oils and greases, using standardized scientific methods. Results: The study revealed significant differences between the sampling points. The concentration of thermotolerant coliforms downstream exceeded environmental quality standards, indicating considerable bacterial contamination due to untreated domestic discharges. BOD5 and COD values were also higher downstream, reflecting an increase in organic pollution. Oils and fats remained within acceptable limits but were higher downstream compared to upstream. Conclusion: The results show the negative impact of untreated domestic wastewater on the Ichu River, with elevated levels of thermotolerant coliforms and organic pollution downstream. The study highlights the urgent need for corrective measures to improve water quality and protect both public health and the aquatic ecosystem.